What Does Reflection Look and Feel Like for International Students? : An Exploration of Reflective Thinking, Reflexivity and Employability - Barton, Georgina; Ryan, Mary (Journal of International Students, 2020)
Reflection, reflective thinking and reflexivity have received significant attention in the scholarly literature on higher education yet there is limited research that explores these concepts in relation to international students. This paper consequently explores what reflection and reflective thinking might look and feel like for international students. We theorize the importance of supporting international students in becoming reflexive practitioners in their chosen area of study; particularly in respect to graduate attributes including reflection and employability. The paper attends to this theorization by sharing Rodgers’ (2002) four functions of reflection, a reflective thinking model – the 4Rs – as well as Archer’s (2000, 2012) notion of reflexivity. We explore how higher educators might consider these frameworks comprehensively when working with international students particularly in the area of workplace experience.